The Behavioural Homogeneity Evaluation Framework: multi-level evaluations of consumer involvement in international segmentation - Broderick, Amanda J; Greenley, Gordon E; Mueller, Rene Dentiste (Journal of International Business Studies, 2007)
This paper presents a generic strategic framework of alternative international marketing strategies and market segmentation based on intra- and inter-cultural behavioural homogeneity. Consumer involvement (CI) is proposed as a pivotal construct to capture behavioural homogeneity, for the identification of market segments. Results from a five-country study demonstrate how the strategic framework can be valuable in managerial decision-making. First, there is evidence for the cultural invariance of the measurement of CI, allowing a true comparison of inter- and intra-cultural behavioural homogeneity. Second, CI influences purchase behaviour, and its evaluation provides a rich source of information for responsive market segmentation. Finally, a decomposition of behavioural variance suggests that national-cultural environment and nationally transcendent variables explain differences in behaviour. The Behavioural Homogeneity Evaluation Framework therefore suggests appropriate international marketing strategies, providing practical guidance for implementing involvement-contingent strategies.